Synthesis, structure, and electrochemical properties of the Ni(OH)\(_2\)/NiMoO\(_4\) composite on the rGO/NF template for hybrid battery-supercapacitor electrodes - ASIH, Retno; NURDIANSAH, Haniffudin; SIANIPAR, Rogabe; GAYATRI, Ida Ayu; NOEROCHIM, Lukman; SUSANTI, Diah; WATANABE, Isao; DARMINTO, Darminto (Journal of Metals, Materials and Minerals, 2026)
The growing demand for renewable and sustainable energy has intensified research on advanced energy-storage systems that can deliver both high energy and power densities. In this study, a Ni(OH)2/ NiMoO4 composite on a reduced graphene oxide/nickel foam (rGO/NF) template was synthesized through a hydrothermal and electrodeposition route to construct a hybrid battery-supercapacitor electrode. The unique hierarchical design combines the pseudocapacitive activity of Ni(OH)2/NiMoO4 with the excellent conductivity of rGO and the high surface area of NF, enabling efficient electron and ion transport. Structural and morphological analyses confirm the successful formation of the Ni(OH)2/NiMoO4/rGO/NF architecture. The electrode exhibits a specific capacitance (Cs) of 358 F∙g‒1 at 5 mV∙s‒1, an energy density of 24 Wh∙kg‒1, a power density of 626 W∙kg‒1, a conductivity of 1.30 S∙m‒1 (0.01 kHz), and retains 86% capacitance after 50 cycles. These findings demonstrate that the synergistic integration of multiredox Ni(OH)2/NiMoO4 with conductive rGO/NF enhances electrochemical performance, providing effective design strategy for developing hybrid battery-supercapacitor electrodes.